Exploration of Pancasila Value in The Traditional Games of Gala-Gala as Strengthening Young Generation Characters - Kusuma Putri; I Putu Adi Permana Putra (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
Pancasila as a basis and ideology of the nation has demonstrated its role in leading citizens' attitudes life in filling every process of life. Pancasila became a guide to the life of a nation projected through its people's attitudes always have some noble value as a starting capital in building civilization. Strengthening the value of the nation's younger generation of character is valued highly, using mainly indigenous knowledge (non-western knowledge) based on local wisdom to build a paradigm of thought and attitude. One form of Nusantara's local wisdom that contributes to ideas in affirmation the character of the nation is through game. The gala-gala as traditional Balinese game has demonstrated its role in giving life learning about the values of life that have relevance to strengthening character for the nation's younger generation. The study examined the exploration of Pancasila values in traditional gala-gala folk games as an effort to strengthen the character of Indonesia's younger generation. The method used in this study is descriptive analysis, which means in both descriptive and analysis of the theme under discussion. The result this study is concept of reinforce the character of the younger generation based on Pancasila values in gala-gala traditional game.